2019
DOI: 10.3390/w11112322
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Deriving the Exact Distribution of Maximum Annual Daily Precipitation

Abstract: Maximum annual daily precipitation does not attain asymptotic conditions. Consequently, the results of classical extreme value theory do not apply to this variable. This issue has raised concerns about the frequent use of asymptotic distributions to model the maximum annual daily precipitation and, at the same time, has rekindled interest in deriving and testing its exact (or non-asymptotic) distribution. In this review, we summarize and discuss results to date about the derivation of the exact distribution of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…As an alternative to the recently questioned EVT (De Michele, 2019;Veneziano et al, 2009), some studies are turning to non-extreme distributions (Papalexiou, 2018;Zaghloul et al, 2020) or proposing alternative distributions that relaxes the asymptotic assumptions, assuming a known parent distribution F(x) of ordinary rainfall events (Miniussi & Marani, 2020). Here, based on the recent finds of Papalexiou (2022) and Marra et al (2023) and on physical reasoning (Wilson & Toumi, 2005), we assumed (and further verified) that the tail of the distribution of rainfall events is stretched-exponential or follows a Weibull distribution tail (Equation 1).…”
Section: Parametric Approach-assessing Changes In Extreme Rainfall Ev...mentioning
confidence: 99%
“…As an alternative to the recently questioned EVT (De Michele, 2019;Veneziano et al, 2009), some studies are turning to non-extreme distributions (Papalexiou, 2018;Zaghloul et al, 2020) or proposing alternative distributions that relaxes the asymptotic assumptions, assuming a known parent distribution F(x) of ordinary rainfall events (Miniussi & Marani, 2020). Here, based on the recent finds of Papalexiou (2022) and Marra et al (2023) and on physical reasoning (Wilson & Toumi, 2005), we assumed (and further verified) that the tail of the distribution of rainfall events is stretched-exponential or follows a Weibull distribution tail (Equation 1).…”
Section: Parametric Approach-assessing Changes In Extreme Rainfall Ev...mentioning
confidence: 99%
“…The four distributions tested are the Gamma, the left-truncated Cauchy, the Uniform, and the Generalized Pareto. The Gamma distribution has a smoothly varying form and it is commonly adopted for description of skewed hydrological variables, such as precipitation depth of wet days (Chow et al 1988). For example, it is usually used to fit monthly aggregated precipitation data in the computation of the SPI.…”
Section: Setup Of Simulation Studymentioning
confidence: 99%
“…Upper extreme quantiles are used, for example, in the design of hydraulic structures. Structures like sewers and dams require design return periods between 2 and 10 years, and between 500 and 10000 years respectively (Chow et al 1988). Due to the limited length of time series, typically 50-90 years (Apipattanavis et al 2010), the quantile of interest is often not observed in the time series (Brazdil and Kundzewicz 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Note that the methodology discussed in our article, can be applied to other statistical distributions related to the extreme value analysis. On this regard, we mention two articles [13,14]. In [13], a useful software for regional and at-site statistical analyses of annual maxima time series is proposed.…”
Section: Introductionmentioning
confidence: 99%
“…The software showed good performance with the annual maxima series for the Italian rain-gauge network by implementing Gumbel, GEV and Two Component Extreme Value distributions. In [14], the results about the derivation of the exact distribution of maximum annual daily precipitation are summarized and discussed, with special attention on compound/super statistical distributions. The results have a 20% higher accuracy in terms of the Root Mean Square Error (RMSE) value, compared to the Naive approach [11].…”
Section: Introductionmentioning
confidence: 99%